Energy efficiency of a variable speed of the centralized air conditioning system using PID controller - Nasution, Henry (Penerbit UTM Press, 2016)
PID control system for air-conditioning system in residence is presented in this manuscript. The control strategy is focused on low energy consumption and thermal comfort for indoor user. The algorithm is developed to control the compressor speed at an appropriate speed according to the temperature inside the controlled area using PID controller. Software is developed to measure and interface the system with controlling the system according to the algorithm. The temperature settings are 20, 22 and 24°C with internal heat load of 0 and 1000 Watt. The results obtained proved that the technique can lower the energy consumption and increased temperature control for better thermal comfort compared to on/off controller.